NILAI SOSIAL DAN RELIGIUS DALAM TRADISI BARODAK PADA MASYARAKAT SAMAWA DI DESA MAPIN REA KECAMATAN ALAS BARAT (STUDI KASUS DI DESA MAPIN REA KECAMATAN ALAS BARAT KABUPATEN SUMBAWA) - Hariz, Abdul; Muhammad Ilyas; Suud; Masyhuri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Research objectives: (1) to know the process of the Barodak tradition (2) to know the social values in the Barodak tradition (3) to know the religious values in the Barodak tradition. This research uses a qualitative approach with a case study research method. The type of data in this research uses primary data and secondary data. The data contained in this research comes from subjects and expert informants with data collection techniques using interview techniques followed by observation and documentation. Data analysis uses qualitative analysis techniques with stages of data reduction, data presentation and drawing conclusions. The results of the research show that (1) there are 3 processes in the barodak tradition, namely preparation of the barodak, implementation of the barodak and closing of the barodak. (2) There are 3 social values in the barodak tradition, namely human values, freedom values and solidarity values. (3) There are 4 religious values In the Barodak tradition, namely the value of worship, moral value, trust value and sincerity value.Keywords: Barodak Tradition Process, Barodak Tradition Social Values, Barodak Tradition Realistic Values.